OPTIMISASI EASE GERAK KROMA1'OGRAF1 CAIR KINERJA TINGG1 UNTUK PEMISAHAN CAMPURAN GLUKOSA, FRUKTOSA, DAN SUKROSA - Made Astri Septiarini, Ni
Mixtures of glucose, fructose, and sucrose are commonly found in various foods of natural product, such as sweet potato, green bean, and various fruits. Glucose, fructose, and sucrose are soluble in water. To analyse such mixtures was rather difficult due to their similar polarity. This research aimed to obtain an optimum system of high performance liquid chromatography (HPLC). The investigation was excecuted by analyzing the mixtures using combinations of acetonitrile and water at various ratios and pHs as mobile phase, and Inertsil NH2 column of room temperature and of 43.6°C. The combination of acetonitril-water at a ratio of (1: 0,15) could separate the three sugars with a retentiom time for glucose 9.77 minutes, fructose 11.53 minutes, sucrose 19.12 minutes, while acetonitrile-buffer solution of pH 4.6 at a ratio of (1 : 0.22) with a column temperature of 43.6°C gave a retention time for glucose 11.35 minutes, fructose 13.45 minutes, and sucrose 24.85 minutes. It was concluded that a decrease in composition of water in the combinations of acetonirile and water and a decrease in pH buffer of the mobile phase caused an increase in the retention time of the three sugars.